Effectiveness of 6-Week Nordic Walking Training on Functional Performance, Gait Quality, and Quality of Life in Parkinson’s Disease - Justyna Szefler-Derela; Michal Arkuszewski; Andrzej Knapik; Dagmara Wasiuk-Zowada; Agnieszka Gorzkowska; Ewa Krzystanek (Medicina, 2020)
Background and objectives: Motor rehabilitation improves physical mobility and quality of life in Parkinson’s disease (PD). As specialized rehabilitation is expensive and resource-consuming, there is a need for simpler, cost-effective methods. The purpose of the study was to determine whether Nordic Walking (NW) training may support the management of motor disability in PD. Materials and Methods: Forty patients (median age 64.0 years, range 50–75 years) with idiopathic PD, Hoehn and Yahr stages II–III, were randomly assigned to NW or standard rehabilitation (SR) programs, comprising twelve rehabilitation sessions conducted bi-weekly throughout the 6-week study period. Results: Median Unified Parkinson’s Disease Rating Scale part III scores were significantly reduced with NW, by 8.5, and with SR, by 6.0 points (both p < 0.001), with significantly greater improvement with NW than with SR (p = 0.047). Gait quality and balance control, measured using the Dynamic Gait Index, improved with NW by a median of 8.0 and with SR by 5.5 points (both p < 0.001), with slightly greater improvement with NW, compared to the SR group (p = 0.064). Quality of life, assessed using the Parkinson’s Disease Questionnaire (PDQ-39), improved with NW by a median of 15 and with SR by 12 points, p = 0.001 and p = 0.008, respectively. Conclusions: The 6-week Nordic Walking program improves functional performance, quality of gait, and quality of life in patients with PD and has comparable effectiveness to standard rehabilitation.